(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
The ionizations of the \(1S\) and \(nS\) states of the atomic hydrogen have been carried out using the hybrid theory, which is variationally correct and has been obtained by modifying the method of polarized orbitals. Earlier, we calculated cross sections of exciting the higher states from the ground state, and cross sections of photoabsorption. Now, we apply the same approach to the ionization of states. The distortion of the orbit is considered due to the incident positron or electron. The distortion takes place whether the incident particle is outside or inside the orbit. Temkin considered distortion of the target electron only when the incident particle is outside the orbit of the target. However, there is no simple way to consider distortion of \(nS\) states of atomic hydrogen. The cross sections are calculated by considering the distortion in the initial state as well as in the final state only in the \(1S\) state and are compared with the previous calculations and the experimental results. The present cross sections have a maximum at an energy which is the same as the incident energy in the experimental results.